COBALAH MENGERTI AND MY IMMORTAL: AN INTERTEXTUALITY STUDY - Santi Tri Wulansari; Lusia Kristiasih Dwi Purnomosasi; Vita Vendityaningtyas (English Teaching Journal : A Journal of English Literature, Language and Education, 2016)
The purpose of this research is to analyze an intertextuality study toward Cobalah Mengerti and My Immortal video clip. Visually, Cobalah Mengerti is similar to My Immortal, but lyrically Cobalah Mengerti is difference than My Immortal. Then, both videos are observed into allusion, reference, and plagiarism of intertextuality. The aims of the research are analyzing the similarities and differences of visual elements and Indonesia society perspective in looking at Cobalah Mengerti and My Immortal achivement.